2017
DOI: 10.1177/1363459317708823
|View full text |Cite
|
Sign up to set email alerts
|

Representations of mental health and arts participation in the national and local British press, 2007–2015

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. AbstractWe analysed news articles published in national and local British newspapers between 2007 and 2015 to understand 1) how mental health and arts participation were framed and 2) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…This study uses a Corpus‐Assisted Critical Discourse Analysis to examine the language of web‐based cancer care pathways information in Norway. This is a ‘tried and tested’ mixed methods approach (Crawford, Gilbert, Gilbert, Gale, & Harvey, 2013) which has become established over the last 15 years (see Adolphs, Brown, Carter, Crawford, & Sahota, 2004; Atanasova, Koteyko, Brown, & Crawford, 2017; Crawford, Brown, & Harvey, 2014). Typically, the approach combines analysis of word frequencies and concordance lines using corpus analysis software to identify the ‘linguistic fingerprint’ or ‘aboutness’ of the text (Scott, 2006) prior to further qualitative discourse analysis.…”
Section: The Studymentioning
confidence: 99%
“…This study uses a Corpus‐Assisted Critical Discourse Analysis to examine the language of web‐based cancer care pathways information in Norway. This is a ‘tried and tested’ mixed methods approach (Crawford, Gilbert, Gilbert, Gale, & Harvey, 2013) which has become established over the last 15 years (see Adolphs, Brown, Carter, Crawford, & Sahota, 2004; Atanasova, Koteyko, Brown, & Crawford, 2017; Crawford, Brown, & Harvey, 2014). Typically, the approach combines analysis of word frequencies and concordance lines using corpus analysis software to identify the ‘linguistic fingerprint’ or ‘aboutness’ of the text (Scott, 2006) prior to further qualitative discourse analysis.…”
Section: The Studymentioning
confidence: 99%
“…Focusing on “the illness side” of mental health, researchers have consequently paid little attention to “the wellness side.” Exceptions include studies by Aragonès et al (), Atanasova et al (), Goulden et al (), Henson et al (), Kenez, O'Halloran, and Liamputtong (), McGinty et al (), Thornicroft et al (), and Whitley and Berry (). Such studies typically provide little detail regarding the precise content of recovery messages and tend to be limited to giving quantitative information about the prevalence of recovery themes.…”
Section: Content: Recent Research and Future Directionsmentioning
confidence: 99%
“…Such studies typically provide little detail regarding the precise content of recovery messages and tend to be limited to giving quantitative information about the prevalence of recovery themes. A more in‐depth analysis of both the qualitative characteristics and frequency of recovery messages in newspapers is available in Atanasova, Koteyko, Brown, and Crawford's () study, which identified a dominant theme of “recovery” emphasising that mental illness can be treated similarly to physical illness including through arts participation. The concept of “recovery” is built on a strong belief that it is possible for people with mental disorders to regain a meaningful life despite persistent symptoms (World Health Organization, ).…”
Section: Content: Recent Research and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of the related insights of social movement theorists who have built on Goffman's conception of frames to theorize and research social movements (Benford & Snow, 2000; Snow & Benford, 1988; Snow, Rochford, Worden, & Benford, 1986) will not be considered because space is limited. Neither shall we consider how scholars in communication studies and journalism have adapted frame analysis to analyse media communications (Atanasova, Koteyko, Brown, & Crawford, 2019a, 2019b; Baroutsis, 2019; Matthes, 2009; Walter, Ophir, & Jamieson, 2020).…”
Section: Introductionmentioning
confidence: 99%